2010
DOI: 10.1021/ma100889p
|View full text |Cite
|
Sign up to set email alerts
|

Flow Accelerates Interfacial Coupling Reactions

Abstract: Reactive coupling of functional polymer chains has been reported to be 3 orders of magnitude slower at static interfaces than under mixing conditions, and the reaction rates under mixing are close to the rates measured in homogeneous melts [Jeon et al. Prog. Polym. Sci. 2005, 30, 939]. However, due to the complexity of interfacial area generation during mixing, it was difficult to isolate the effects of flow on reaction kinetics. In this paper, a reactive multilayer system was created to explore this issue. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…As shown in Figures 8a, b, coextrusion accelerates the coupling reaction for all types of functional PEs. Similar phenomena were found in the literature where the coupling reaction between an amine-terminal polystyrene (PS-NH 2 ) and an anhydride-terminal polymethyl methacrylate (PMMA-anh) bilayer took about 1 h for the interface to be saturated with block copolymers, whereas when these two polymers were melt blended 11,28 or multilayer coextruded, 8 it took less than 1 min (i.e., about two orders of magnitude faster compared to quiescent annealing). For the coextrusion experiments reported here, the reaction acceleration occurs during laminar flow without mixing.…”
Section: Reaction Acceleration Through Coextrusionsupporting
confidence: 83%
See 1 more Smart Citation
“…As shown in Figures 8a, b, coextrusion accelerates the coupling reaction for all types of functional PEs. Similar phenomena were found in the literature where the coupling reaction between an amine-terminal polystyrene (PS-NH 2 ) and an anhydride-terminal polymethyl methacrylate (PMMA-anh) bilayer took about 1 h for the interface to be saturated with block copolymers, whereas when these two polymers were melt blended 11,28 or multilayer coextruded, 8 it took less than 1 min (i.e., about two orders of magnitude faster compared to quiescent annealing). For the coextrusion experiments reported here, the reaction acceleration occurs during laminar flow without mixing.…”
Section: Reaction Acceleration Through Coextrusionsupporting
confidence: 83%
“…Therefore, the reaction rate between two immiscible reactive polymers in a molten interface was significantly higher than that of small molecule analogues in solution. Zhang et al 8 and Feng and Hu 28 also observed similar phenomena. This is not surprising considering increased collision probability originating from longer relaxation time of reactive polymer chains holding functional groups at the interface.…”
mentioning
confidence: 61%
“…It has been suggested that the interface can be improved by the use of block copolymer compatibilizers to prevent delamination in this system [34,48].…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 8 1 We note that a significant spontaneous delamination between the PMMA and PS layers occurred after two months of the samples sitting at ambient conditions in the lab, apparently due to the low interfacial adhesion between the immiscible PS and PMMA layers [34]. presents the T g corrected reinforcements of flow and transverse directions.…”
Section: Reinforcement Of a Single Graphene Filled Pmma Layermentioning
confidence: 93%
“…A detailed description of the co-extrusion line can be found in the literature. 3,[6][7][8][9] On the basis of the continuity equation, melt velocity in the co-extrusion dies can be deduced from the chill-roll speed and film thickness. At a total flow rate of 38.4 cm 3 min À1 as determined from gear-pump rotation rate, the residence time of the interface traveling at equal flow rates was determined to be 9-13 s by using the method described by Song et al 3 Upon exiting the die land, bilayer films were drawn by stainless steel rolls chilled at 4 1C.…”
Section: Co-extrusionmentioning
confidence: 99%